The ASEAN Economic Community A Conceptual Approach - Pelkmans, Jacques 1946- (Cambridge University Press, 2016)
The Association of Southeast Asian Nations (ASEAN) has experienced rapid economic growth for many years. Although the population of ASEAN is larger than the EU-28, the emerging ASEAN market, called the ASEAN Economic Community (AEC), is still little understood by policy makers in many parts of the world, by business professionals and students, as well as by scholars in economics, business, politics and economic law. This book provides, for the first time, a rigorous analytical approach of the new AEC and its intricacies. It sets out its ambition, scrutinises its economic integration logic and detects its deficits. Besides a detailed analysis of the AEC Roadmap, the book also elaborates on its achievements. Several strategic economic options for the AEC, in particular as an instrument to accelerate the economic development of the region, are explored
Title from publisher's bibliographic system (viewed on 08 Mar 2016)